Electricity Tariffs for Nonresidential Customers in Sub-Saharan Africa - Kojima, Masami; Han, Jace Jeesun (World Bank, Washington, DC, 2017)
The aggregate price per kilowatthour charged to commercial and industrial customers varies by a factor of more than 20 across 38 Sub-Saharan African countries studied. Tariff schedules also show large differences: Nearly half the countries do not use time-of-use pricing, about a fifth have no demand charges, and three have neither demand nor fixed charges for any customer category. As Africa's power sector develops, there is considerable scope to tailor tariff schedules to meet the needs of different customers, reduce the costs of supply, and ensure minimum revenues from medium-size and large customers. Doing so would strengthen utilities' financial health and increase the quantity and quality of electricity delivered.